MORPHOLOGY EFFECT ON BEHAVIOUR OF PHOSPHORICACIDIN SUPRAMOLECULAR STRUCTURED POLYMER MEMBRANE FUEL CELL - Sunit Hendrana; Febrina Tri Hartanti; Iman Rahayu (Jurnal Sains Materi Indonesia, 2013)
MORPHOLOGY EFFECT ON BEHAVIOUR OF PHOSPHORICACIDIN SUPRAMOLECULAR STRUCTURED POLYMER MEMBRANE FUEL CELL. Study on the effect of morphology on the conductivity of small molecules added polymer membrane for fuel cell has been done. The polymer electrolyte membrane fuel cell was made by constructing of supramolecular interaction between sulfonated polystyrene and polyethylene-graft-maleic anhydride. The small molecules used was benzimidazole and phosphoric acid. The addition of benzimidazole and phosphoric acid, was espected to improve to ionic conductivity. However, in this work it was observed that morphology of the membrane play vital roles in the final properties of the membrane. In other words, beside concentration of phosphoric acid the morphology affects the conductivity of polymer membrane fuel cell.